The mediating effect of perceiving close relatives as obese on obesity and weight control behavior score among adults: An exploratory cross-sectional study in Chongqing, China - Wu, Tingting; Liu, Weiwei; Chen, Yifan; Guo, Tian; Sun, Rong (Frontiers in Public Health, 2022)
Obesity is one of the most glaringly obvious, yet most neglected, public health problems the world is facing today. Individuals' self-perception of being overweight is essential to engaging in weight control behavior. This is the first exploratory study in Chongqing to assess the mediating effect of perceived obesity in close relatives on obesity and weight control behavior among adults. A cross-sectional study, including 3,7492 participants, was conducted in a healthcare center in Chongqing, China. For Kruskal–Wallis test analyses, logistic regression and Sobel-Goodman mediation tests were employed. Only 1.76% of participants (660) were medically identified as obese, and only 2.13% of participants (798) thought their close relatives were obese. Nearly one-third of the participants consumed more than double the daily recommended amount of meat. More than 85% of participants were physically inactive. Obesity was positively associated with obesity perception in close relatives (OR = 19.556, P < 0.001). The association between the respondent's obesity status and weight control behavior scores changed statistically significantly (β = 0.594, P < 0.001). Individuals who perceived their close relatives as obese were more likely to engage in weight control behavior themselves (β = 0.678, P = 0.001). The obesity perception in close relatives partially mediated the association between obesity and weight control behavior (ab = 0.141, SE = 0.03, 95% CI = 0.086, 0.198). Obese people are more likely to engage in weight control behaviors. The effect of individuals' obesity status on weight control behavior scores is partially mediated by the obesity perception in close relatives among the participants. Findings suggest that personal obesity status perceptions of close relatives might provide new weight management ideas for healthcare centers.